2012
DOI: 10.1021/bm201509b
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Induced Self-Assembly of Native Silk Proteins into Fibrils Studied by Atomic Force Microscopy

Abstract: Noncontact mode atomic force microscopy was used to investigate native silk proteins prepared in different ways. Low protein concentrations revealed that single protein molecules exhibit a simple, round shape with apparent diameters of 20-25 nm. Shearing the native protein solutions after extraction from the gland and prior to drying led to a beads-on-a-string assembly at the nanometer scale. Protein concentration had a significant effect on the morphology of the protein assemblies. At higher protein concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
137
1
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(161 citation statements)
references
References 47 publications
14
137
1
9
Order By: Relevance
“…To date, computational calculations 4 , X-ray diffraction 5 , nuclear magnetic resonance 6 , polarized light microscopy 7 , scanning electron microscopy 7,8 , transmission electron microscopy 9 , Raman spectromicroscopy 10 and, more recently, atomic force microscopy (AFM) [11][12][13][14][15][16][17] have been the most commonly used techniques to study the nanoarrangements of silk fibre domains. However, the details of the size, topology, mechanical features and fractional composition of the crystalline and amorphous domains remain to be clarified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, computational calculations 4 , X-ray diffraction 5 , nuclear magnetic resonance 6 , polarized light microscopy 7 , scanning electron microscopy 7,8 , transmission electron microscopy 9 , Raman spectromicroscopy 10 and, more recently, atomic force microscopy (AFM) [11][12][13][14][15][16][17] have been the most commonly used techniques to study the nanoarrangements of silk fibre domains. However, the details of the size, topology, mechanical features and fractional composition of the crystalline and amorphous domains remain to be clarified.…”
mentioning
confidence: 99%
“…With the advent of AFM, researchers are now pursuing investigations of the structural and mechanical nanodomains of spider silks, particularly in their near native condition. Previous investigations of the nanostructure of spider silks by AFM focused on the qualitative topographical imaging of sectioned 11 , dissociated 12 , reassembled 13 or synthetic 14 silk fibres.…”
mentioning
confidence: 99%
“…An exception is egg sack silk produced by the B. mori larva. This type of silk has an intrinsic softening behavior (N = 0.3-0.5) and displays fibril diameters of 8-100 nm [38]. This is clearly underestimated by our model, which predicts a critical size of only a few nanometers.…”
Section: Generalization To Fibrous Biomaterialsmentioning
confidence: 63%
“…In terms of the relation with supercontraction, it has been suggested that the production of silk with different tensile properties can increase the survival ability of the spider [72,103]. Recent experimental findings indicated that protein concentration had a significant effect on fibril morphology [54], whereas active control on the properties of the fibre during spinning [18] (rather than protein sequence) would allow an efficient adaptation of the properties of silk to the environment and local requirements. As such, spider speciation and silk type would dictate the fribril/fibre structure.…”
Section: Resultsmentioning
confidence: 99%
“…As such, I use a coarse-grain mesoscopic 'bead-on-a-string' model as a platform to assess silk fibril behaviour, using general MD formulations [28,32]. Experimentally, it has been demonstrated that shearing of the silk protein solution can lead to a similar bead-on-a-string assembly at the nanometre scale [54,55]. Through the total potential energy of the fibril, f the energetic contributions of the model can be simply described as f ¼ f fibril þ f contact , where the fibrils are represented by particle-spring chains with defined axial behaviour (f fibril ) and interfibril repulsive pairwise interactions (f contact ).…”
Section: Methodsmentioning
confidence: 99%